A New Twist to an Age-Long Friendship: The Role of Local Defence Groups in the Conflict Between Farmers and Herders - Bamidele, Seun (Southern African Journal of Security, 2024)
The relationship between farmers and herders, once characterised by symbiosis and mutual dependence, has undergone a profound transformation in many regions worldwide, marked by escalating tensions and violent conflicts over resources. This paper examines a new twist to the long-standing relationship, focusing on the emerging phenomenon of local defence groups and their impact on the dynamics of conflict between farmers and herders. Drawing on a multidisciplinary approach, this study explores the origins, motivations, organisational structures, and strategies of local defence groups operating within the context of farmer-herder conflicts using a qualitative approach that relies on secondary data from scholarly journals and newspaper editorials. The data was analysed using thematic analysis. The study established that historical grievances, socioeconomic factors, and environmental pressures fuel the emergence of these groups, often as a response to perceived failures of formal security mechanisms. This research assesses the implications of local defence groups for conflict escalation, peacebuilding efforts, and governance dynamics. While these groups may offer immediate security to communities vulnerable to violence and theft, their actions can exacerbate tensions, perpetuate cycles of revenge, and undermine prospects for long-term peace and stability. Additionally, their interactions with formal authorities, including the police and military, raise questions about state legitimacy, rule of law, and human rights protections. Through a nuanced analysis of case studies from diverse regions affected by farmer-herder conflicts, this study sheds light on the complexities of local defence dynamics. It offers insights for policymakers, practitioners, and scholars alike. It underscores the importance of holistic approaches that address underlying drivers of conflict, promote dialogue and reconciliation, and strengthen governance structures to foster sustainable peace and coexistence between farmers and herders in the face of evolving challenges.